2018
DOI: 10.1186/s13195-018-0338-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel botanical drug DA-9803 prevents deficits in Alzheimer’s mouse models

Abstract: BackgroundAlzheimer’s disease (AD) is a neurodegenerative disorder characterized by deposition of amyloid plaques and disruption of neural circuitry, leading to cognitive decline. Animal models of AD deposit senile plaques and exhibit structural and functional deficits in neurons and neural networks. An effective treatment would prevent or restore these deficits, including calcium dyshomeostasis observed with in-vivo imaging.MethodsWe examined the effects of DA-9803, a multimodal botanical drug, in 5XFAD and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
5
21
0
Order By: Relevance
“…The results of this study showed a significant decrease in SAP% in the AD group compared to the control group. This finding was in agreement with Pagnier et al [29] who found a decrease in alteration behavior at Y-the maze in an AD mice model.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed a significant decrease in SAP% in the AD group compared to the control group. This finding was in agreement with Pagnier et al [29] who found a decrease in alteration behavior at Y-the maze in an AD mice model.…”
Section: Discussionsupporting
confidence: 93%
“…1o, Mann Whitney test, p<0.001). Since we had verified that neither NB-02 nor vehicle interfered with methoxy-X04 binding to individual plaques [13], decreases in plaque intensity signaled bona fide plaque clearance in NB-02 condition.…”
Section: Gfap Andmentioning
confidence: 87%
“…All the studies complied with Massachusetts General Hospital Animal Care and Use Committee as well as NIH guidelines for the use of laboratory animals. APP/PS1 mice underwent intracortical virus injections followed by cranial window installations over the right hemisphere [15] on the same day starting at 7 months of age similar to earlier reports [11,13,16,17]. Following anesthesia induction, animals were secured in a stereotaxic apparatus.…”
Section: Animals and Surgerymentioning
confidence: 99%
See 2 more Smart Citations